Using an Activity Based on Constructivism To Help Students Develop a More Integrated Understanding of Cell Signaling Pathways - Laura MacDonald (American Society for Microbiology, 2019)
In subjects like cell biology, genetics, and immunology, a solid understanding of signal transduction is key to mastering new content.  Often times students’ approach to learning signal transduction pathways relies heavily on memorization.  In this paper, we describe a modular method to introduce students to signal transduction.  In this method, students are first presented with the discreet building blocks or molecules that comprise signaling pathways (such as the vocabulary terms signal molecule, receptor, effector and target) and asked to integrate the knowledge by building (“do it yourself” or DIY) their own signaling pathway.  Students are then given the opportunity to learn about each other’s pathways to identify ways in which they overlap and diverge.  Ultimately, students are given the task to search the literature to identify a real-world example that mimics or is very similar to the pathway they came up with and note similarities and differences.  We find this is a way to foster students integrating signal transduction knowledge.